Treasure Island - Stevenson, Robert Louis (Lahore Readingd, 2016)
Part adventure tale and part coming-of-age story, Treasure Island follows Jim Hawkins as he embarks on a sea adventure after obtaining a treasure map.
Keywords: Treasure troves -- Caribbean Area -- Sea stories